2020
DOI: 10.1021/acschemneuro.0c00150
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA GAS5 and miR-137 Polymorphisms and Expression are Associated with Multiple Sclerosis Risk: Mechanistic Insights and Potential Clinical Impact

Abstract: The pathogenesis of multiple sclerosis (MS) is influenced by the interaction of genetic and epigenetic mechanisms. The long noncoding RNA GAS5 acts as a competing endogenous RNA for microRNA-137 and is involved in demyelination. We investigated the association of GAS5 and miR-137 expression and their polymorphisms with MS susceptibility. One hundred and eight MS patients and 104 healthy controls were included. Expression analysis and genotyping of GAS5-rs2067079 and miR-137-rs1625579 single nucleotide polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…Most of the mutations are typically located in either coding gene regions with an influence on protein function or noncoding gene regions, potentially affecting a targeted gene transcript. Additionally, recent studies suggested that functional variants occurring in microRNA sequences were associated with susceptibility to AD [6][7][8][9][10][11][12][13][14][15]. These findings indicate that variants in common miRNAs could be genetic markers of AD such as multiple sclerosis, rheumatoid arthritis, and ankylosing spondylitis, which highlighted a new paradigm for genetic susceptibility.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Most of the mutations are typically located in either coding gene regions with an influence on protein function or noncoding gene regions, potentially affecting a targeted gene transcript. Additionally, recent studies suggested that functional variants occurring in microRNA sequences were associated with susceptibility to AD [6][7][8][9][10][11][12][13][14][15]. These findings indicate that variants in common miRNAs could be genetic markers of AD such as multiple sclerosis, rheumatoid arthritis, and ankylosing spondylitis, which highlighted a new paradigm for genetic susceptibility.…”
Section: Introductionmentioning
confidence: 92%
“…Among them, 56 studies were eliminated since they did not contain sufficient genotype results (n = 18) or for not investigating an association between miRNA-SNP and AD risk (n = 17) or for being a review or meta-analysis (n = 13), expert opinion (n = 3), or case report (n = 5). Ultimately, 94 articles met all the inclusion criteria for our meta-analysis, of which 87 were eligible for quantitative analysis of risk estimates [6][7][8][9][10][11][12][13][14][15]. Assessment of interinvestigator agreement using kappa values for the selected articles yielded values of 0.84 for PubMed, 0.88 for Embase, 0.90 for Web of Science, 0.91 for Google Scholar, and 1.0 for CNKI, suggesting a high level of agreement between our two reviewers.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…miRNAs can control many immune processes, including T- and B-cell development and maturation, antigen presentation, Toll-like receptor signaling and pro-inflammatory cytokine production, immunoglobulin class-switch recombination in B-cells, and T-cell receptor signaling (Ceribelli et al 2012 ). Differential expression of non-coding RNAs, including miRNAs were found in patients affected by several autoimmune diseases, and were linked to the pathogenesis of these conditions (Senousy et al 2019 ; Senousy et al 2020 ; Abd-Elmawla et al 2020 ). Indeed, dysregulated miRNA expression has been shown to be implicated into the molecular mechanisms of RA (Tavasolian et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs can control many immune processes, including T-and B-cell development and maturation, antigen presentation, Toll-like receptor signaling and pro-inflammatory cytokine production, immunoglobulin class-switch recombination in B-cells, and Tcell receptor signaling (Ceribelli et al 2012). Differential expression of non-coding RNAs, including miRNAs were found in patients affected by several autoimmune diseases, and were linked to the pathogenesis of these conditions (Senousy et al 2019;Senousy et al 2020;Abd-Elmawla et al 2020). Indeed, dysregulated miRNA expression has been shown to be implicated into the molecular mechanisms of RA (Tavasolian et al 2018).…”
Section: Introductionmentioning
confidence: 99%